THE DIAGNOSIS TECHNIQUE OF ABNORMAL HEATING OF POWER CAPACITORS - D. I. Zalizny (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
The existing system of protection and diagnostics are not able to detect abnormal heating of the power capacitors caused by its internal malfunction formation. The paper contains a proposal of a technique that enables to detect such heat at its early study. This technique consists of a hardware and an algorithms. The hardware consists of a microprocessor-based instrument developed by the author, of measuring transformers of current and of temperature sensors. This equipment must be connected to the condenser unit with a rated voltage of 380 V. In operation, the device performs continuous measurement of the surface temperature of the casing of each condenser, the temperature of the external environment, voltage and current from the power source. The measured values are used in the mathematical model of thermal processes that enables to calculate the temperature of the hottest point of each capacitor in real-time. Then the calculation of the intrinsic difference ΔΘ1° between the average temperature values of the dielectric and the base average value of this temperatures during the second day from the start of the measurements. If the Dq1 value exceeds the value of the absolute error of simulation, diagnostic signals of abnormal levels of heating, viz. low, medium, high and very high, are generated. It is also necessary to calculate the rate of change of ΔΘ1° and to consider the values obtained in the formation of hazard levels. For the low level and the average level of hazard the operation of diagnostic system with a visual signal is recommended, while for the high level of hazard it is recommended to use both visual and sound signals, and for the very high hazard level the capacitor ought to be turned off from the source. The algorithms have been developed heuristically. The final formation of the algorithms is possible only after the long-term operation of the proposed diagnosis system on real objects. The implementation of the developed system will reduce the probability of sudden failure of capacitor units and, correspondingly, will increase the reliability of power supply system of enterprise.